Injectable PLGA microspheres with tunable magnesium ion release for promoting bone regeneration. (February 2019) - Yuan, Zuoying; Wei, Pengfei; Huang, Yiqian; Zhang, Wenxin; Chen, Fuyu; Zhang, Xu; Mao, Jianping; Chen, Dafu; Cai, Qing; Yang, Xiaoping
Graphical abstract: Abstract: Magnesium ions (Mg 2+ ) are bioactive and proven to promote bone tissue regeneration, in which the enhancement efficiency is closely related to Mg 2+ concentrations. Currently, there are no well-established bone tissue engineering scaffolds that can precisely control Mg 2+ release, although this capability could have a marked impact in bone regeneration. Leveraging the power of biodegradable microspheres to control the release of bioactive factors, we developed lactone-based biodegradable microspheres that served as both injectable scaffolds and Mg 2+ release system for bone regeneration. The biodegradable microsphere (PMg) was prepared from poly(lactide-co-glycolide) (PLGA) microspheres co-embedded with MgO and MgCO3 at a fixed total loading amount (20 wt%) with different weight ratios (1:0; 3:1; 1:1; 1:3; 0:1). The PMg microspheres demonstrated controlled release of Mg 2+ by tuning the MgO/MgCO3 ratios. Specifically, faster release with higher initial concentrations of Mg 2+ were detected at higher MgO fractions, while long-term sustained release with lower concentrations of Mg 2+ was obtained at higher MgCO3 fractions. All prepared PMg microspheres were non-cytotoxic. Furthermore, they promoted attachment, proliferation, osteogenic differentiation, especially, cell migration of bone marrow mesenchymal stromal cells (BMSCs). Among these microspheres, PMg-III microspheres (MgO/MgCO3 in 1:1) exhibited the strongest promotion of mineral depositions and osteogenic differentiation of BMSCs. PMg-III microspheres were injected into the critical-sized calvarial defect of a rat model, resulting in significant bone regeneration when compared to the control group filled with PLGA microspheres. In the PMg-III group, the new bone volume fraction (BV/TV) and bone mineral density (BMD) reached 32.9 ± 5.6% and 325.7 ± 20.2 mg/cm 3, respectively, which were much higher than the values 8.1 ± 2.5% (BV/TV) and 124 ± 35.8 mg/cm 3 (BMD) in the PLGA group. These findings indicated that bioresorbable microspheres possessing controlled Mg 2+ release features were efficient in treating bone defects and promising for future in vivo applications. Statement of Significance: Magnesium plays pivotal roles in regulating osteogenesis, which exhibits concentration-dependent behaviors. However, no generally accepted controlled-release system is reported to correlate Mg 2+ concentration with efficient bone regeneration. Biodegradable microspheres with injectability are excellent cell carriers for tissue engineering, moreover, good delivery systems for bioactive factors. By co-embedding magnesium compounds (MgO, MgCO3 ) with different dissolution rates in various ratios, tunable release of Mg 2+ from the microspheres was readily achieved. Accordingly, significant promotion in bone defect regeneration is achieved with microspheres displaying proper sustained release of Mg 2+ . The developed strategy may serve as valuable guidelines for bone tissue engineering scaffold design, which allows precise control on the release of bioactive metal ions like Mg 2+ toward potential clinical translation.